Evaluation of the Zakat System as a Tool for Redistribution of Wealth in the Modern Economy - Sugianto, Efendi; Wei, Zhang; Xu, Shanshan (Yayasan Pendidikan Islam Daarut Thufulah, 2024)
Zakat is an important tool in Islamic economics as a way to spread wealth and reduce economic inequality. Evaluating the effectiveness of the zakat system to achieve these goals in the context of a modern global and complex economy is essential. With increasing amounts of wealth concentrated in the hands of a few and increasing economic inequality, it is important to understand the extent to which zakat can help improve a more equitable distribution of wealth. The aim of this research is to assess how effective the zakat system is as a tool for wealth redistribution in a modern economy. The main focus of the research is to assess the extent to which zakat can reduce economic inequality and improve social welfare in society. This research uses several approaches. The concept of zakat in Islamic economics is studied through descriptive analysis; comparative research on the implementation of zakat in several countries; and surveys and interviews with relevant stakeholders to collect empirical data. The impact of zakat on wealth redistribution and economic inequality is assessed through quantitative and qualitative data analysis. The research results show that the implementation of the zakat system in the modern economy has a significant impact in reducing economic inequality. Zakat is effective in shifting wealth from high-income groups to those in greater need, although there are administrative and social challenges during its implementation. The results of the analysis show that zakat plays an important role as a tool for wealth redistribution in the contemporary economy. However, greater efforts are needed to increase awareness, compliance and administrative efficiency in zakat management to reach its full potential. Therefore, this research increases our understanding of the possibilities and obstacles of zakat as an economic tool in today's world.